Identification of molecular targets in the pathogenesis of multiple myeloma / Ivyna Bong Pau Ni - Ivyna , Bong Pau Ni (2017)
Multiple myeloma (MM) is a cancer of plasma cells. It is a highly heterogenous disease composed of numerous molecularly defined subtypes, each with varying clinicopathological features and disease outcomes. In the present study, we performed array comparative genomic hybridisation (aCGH) to identify common copy number variations (CNVs) in 63 MM patients. Our findings revealed CNVs in 100% of patients analysed. Common copy number gains were detected in 1q, 2q, 3p, 3q, 4q, 5q, 6q, 7q, 8q, 9q, 10q, 11q, 13q, 14q, 15q, 21q and Xq while common copy number loss in 14q. Gain of 7q22.3 was the most common CNV (92%) and NAMPT is localised in this region. The CTSS, LYST, CLK1, ACSL1 and NFκBIA are genes localised within the CNVs and they represent novel information that have never been previously described in MM. Interestingly, CTSS is localised in 1q21.2, a frequently gain region which is associated with poor prognosis in MM. Two CNVs (1q42.3 and 7q22.3) were verified by qPCR. By using different cohort of samples, we performed global mRNA and miRNA expression profiling of 27 MM samples (19 clinical specimens and 8 myeloma cell lines) and 3 normal controls by microarray. Both the mRNA and miRNA expressional profiles in the normal and MM were compared to identify potential mRNAs and miRNAs involved in the pathogenesis of MM. The differential miRNA-target was also identified by databases prediction and inverse correlation analysis of the matched miRNA and mRNA expression profiles. A total of 348 differentially expressed mRNAs (≥2.0 fold change; p<0.01) and 1781 miRNAs (≥2.0 fold change; p<0.05) were identified. The reliability of the microarray data was verified for 4 mRNAs (CCNA2, RAD54L, RASGRF2 and HKDC1) and 2 miRNAs (miR-150-5p and miR-4430). Majority of the differentially expressed genes are involved in cell cycle and cell cycle checkpoints, DNA repair, mitotic/ spindle checkpoints, cell proliferation, mismatch repair pathway and kinetochore and microtubule attachment. The HIST2H3A, CYSLTR2 and AURKB were 3 most significant differentially expressed genes, which are localised in the frequently altered chromosomal regions, namely 1q21, 13q14.2 and 17p13.1, respectively. Apart from that, the miR-150 and miR-125b were 2 differentially expressed miRNAs, which are closely related to B cell differentiation and therefore highlighted their critical roles in MM development. The miRNA-target integrative analysis revealed inverse correlation between 5 putative target genes and 15 miRNAs (p<0.05). Interestingly, all 5 target genes, namely RAD54L, CCNA2, CYSLTR2, RASGRF2 and HKDC1 play critical functions in oncogenesis. Apart from that, the biological function of NAMPT in RPMI-8226 myeloma cell line was determined by RNAi approach. The RNAi findings revealed that silencing of NAMPT significantly reduced the mRNA (p<0.05) and protein expression levels (p<0.01) in RPMI-8226 myeloma cells. These scenarios indicated that NAMPT-mediated gene silencing inhibited cell proliferation and induced apoptosis in RPMI-8226 (p<0.05). The present study has expanded our knowledge on the genomic and epigenetic mechanisms underlying the molecular pathogenesis of MM and also opens up clues and avenues for future investigation of myelomagenesis.